Expression profile of late responsive genes induced by spatial learning task: involvement of pathways in locomotion and memory - Teh, Hui-Xin; Then, Sue-Mian; Indah Maisarah Shani; Musalmah Mazlan; Wan Zurinah Wan Ngah; Rahman Jamal (Pusat Perubatan Universiti Kebangsaan Malaysia, 2013)
The altered molecular mechanisms by experimental therapies for neurodegenerative diseases itself could be overlapped with genes induced by the behavioral task. We employed the microarray platform to identify the differentially expressed late responsive genes in medial temporal lobes of four Morris Water Maze (MWM) trained and untrained BALB/c mice. After MWM training, the mice were sacrificed to obtain their brains’ medial temporal lobes. The total RNA was extracted from the tissues and global mRNA gene expression analysis was performed using Affymetrix GeneChip ®Mouse Gene 1.0 ST Array. There were 3635 (62.2%) up-regulated genes and 2206 (37.8%) down-regulated genes at p-values of < 0.05. These genes were operationally defined as late memory-related genes and behavior-related genes indicating that behavioral learning has a significant impact on the gene expression of the medial temporal lobes. From the pathway analysis, the network of memory and locomotion genes, and the guanylate cyclase pathway were identified as one of the most interesting pathways. The qPCR validation showed that the genes NMDA receptor 2a (Nmda2a) and cAMP dependent protein kinase type I beta regulatory subunit (Prkar1b) were up-regulated while adenylate cyclase 5 (Adcy5) was down-regulated. We proposed that the involvement of guanylate cyclase pathway in the long-term potentiation lasted at least up to three days after the MWM test. Present study suggested that the molecular mechanisms followed by spatial learning task could be altered up to three days or even longer, it could be overlapped with genes induced by further invented experimental therapy.